Caracteristicas de la prescripcion - indicación de antibióticos en gestantes del Instituto Nacional Materno Perinatal Julio 2019 - Junio 2021 - Gutierrez Soto, Gustavo (2025)
Objective. To determine the characteristics of the prescription-indication of antibiotics in pregnant women at the Nacional Maternal Perinatal Institute (INMP), July 2019 - June 2021. Materials and Methods. The research was of basic type, deductive method with quantitative approach of non-experimental design, cross-sectional and retrospective. The sample consisted of 328 medical records, the information was collected in a validated instrument, the database was created in Microsoft Excel and then analyzed by the SPSS program. Results.  A moderate level of 73% was identified with respect to antibiotic prescription-indication characteristics. The most frequent indications were preoperative antibiotic prophylaxis (31.7%) and urinary tract infection (28.66%). The obstetrician-gynecologist specialist was the one who prescribed the most (95%) and there was a higher frequency of prescription in pregnant women in the third trimester (82.1%). The most frequently prescribed antibiotics were Betalactam antibiotics with 79.27%; within this group, the most prescribed were Cefazolin 1g injectable in 25.8%; Cephalexin 500 mg tablet in 13.9%. In relation to the risk category according to the Food and Drug Administration (FDA), 93.3% were prescribed category B antibiotics. Conclusion: The characteristics of the prescription - indication were adequate due to the fact that a specialized physician prescribed, taking care with the prescription, indication, posology, type of antibiotic, frequency of antibiotics and their use according to the classification of the FDA risk categories.